Overektomili sıçanlarda metforminin kronik öngörülemeyen hafif stresteki etkisi - Özsağır, Mehmet Haktan (My University, 2025)
Overektomili sıçanlarda metforminin kronik öngörülemeyen hafif stresteki etkisi Amaç: Amacımız, overektomi (OVE) ve kronik öngörülemeyen hafif stres (KÖHS) modeli uygulanan sıçanlarda metforminin; anksiyete benzeri davranışlar ve kognitif belirteçler, hipokampus, prefrontal korteks ve amigdalada sinaptik plastisite, inflamasyon ve apoptoz parametreleri üzerindeki etkilerini araştırmaktır. Gereç ve Yöntem: OVE işleminden 4 hafta sonra sıçanlara 2 hafta boyunca KÖHS protokolü ve birlikte başlanan metformin tedavisi, uygulanmıştır. Davranışsal değerlendirmeler açık alan testi (OFT), yükseltilmiş artı labirent (EPM) ve yeni nesne tanıma testi (NORT) ile, biyokimyasal incelemeler ise ELISA testi ile yapılmıştır. Bulgular: OVE+KÖHS grubunda kontrol ile kıyaslandığında anksiyete düzeyi belirgin şekilde arttı; OFT testinde merkezde geçirilen süre (p<0.01), şahlanma (p<0.01) ve süslenme (p<0.05) sayıları azaldı. EPM testinde OVE+KÖHS grubunda kontrole göre anksiyete indeksi (p<0.01) ve donma süresi (p<0.001) artarken, NORT testinde tanıma belleği zayıfladı (p<0.001). Metformin tedavisi ise bu davranışsal bozuklukları anlamlı düzeyde düzeltti. OVE+KÖHS grubunda, control grubuna göre; hipokampus, prefrontal korteks ve amigdalada BDNF (p<0.01–0.05) ve sinaptofizin (p<0.05) düzeyleri azalırken; kaspaz-9 aktivitesi arttı (p<0.05–0.001). Metformin tedavisi, bu parametrelerde anlamlı bir iyileşme sağladı (p<0.05–0.001). Sonuç: Bulgularımız, OVE+KÖHS modelinde uygulanan metforminin sinaptik plastisiteyi artırdığını, apoptozu azalttığını ve anksiyete benzeri davranışları hafiflettiğini göstermektedir. Metformin, özellikle menopoz sonrası döneme ait psikiyatrik bozuklukların tedavisinde potansiyel bir farmakolojik ajan olarak değerlendirilebilir.

Effect of metformin on chronic unpredictable mild stress in ovariectomized rats studen Objective: Our aim was to investigate the effects of metformin on anxiety-like behaviors and cognitive markers, synaptic plasticity in hippocampus, prefrontal cortex and amygdala, inflammation and apoptosis parameters in rats subjected to ovariectomy (OVX) and chronic unpredictable mild stress (CUMS). Materials and Methods : Four weeks after OVX procedure, the rats were administered the CUMS protocol and metformin treatment for 2 weeks. Behavioral evaluations were performed with open field test (OFT), elevated plus maze (EPM) and novel object recognition test (NORT), while biochemical examinations were performed with ELISA. Results: When compared the control ones in the OVX+CUMS group, anxiety levels markedly increased; time spent in the center (p<0.01), rearing (p<0.01) and grooming (p<0.05) in the OFT decreased. In the EPM, the anxiety index (p<0.01) and freezing time (p<0.001) increased. Recognition memory in the NORT was impaired (p<0.001). Metformin treatment significantly ameliorated these behavioral disturbances (p < 0.01–0.001). In the OVX+CUMS group, compared to control group, BDNF (p<0.01–0.05) and synaptophysin (p<0.05) levels decreased in the hippocampus, prefrontal cortex and amygdala, while caspase-9 activity increased (p<0.05–0.001). Metformin produced significant improvements in these parameters (p<0.05–0.001). Conclusion: Our findings show that metformin treatment applied under the OVX+CUMS model enhances synaptic plasticity, reduces apoptosis and alleviates anxiety‑like behaviors. Metformin might be considered a potential pharmacological agent especially for the treatment of psychiatric disorders in the post‑menopausal period.
Effect of metformin on chronic unpredictable mild stress in ovariectomized rats studen
Keywords: apoptosis; apoptoz; Farmakoloji; inflamasyon; inflammation; Kronik öngörülemeyen hafif stres; metformin; ovariectomy; overektomi Chronic unpredictable mild stress; Pharmacology